Experimental Research on the Transverse Effective Bending Rigidity of Shield Tunnels - Gang Zheng; Yawei Lei; Tao Cui; Xuesong Cheng; Yu Diao; Tianqi Zhang; Jibin Sun (Advances in Civil Engineering)
The uniform rigidity ring model is commonly used to design the segmented structures of shield tunnels. However, model tests have been primarily used to study the transverse effective rigidity ratio η with a concentrated force, which is notably different from realistic loading patterns. To obtain more reasonable η values, in this study, tests were performed with a concentrated load on an experimental bench and with a realistic loading pattern in sandy soil in a rigid steel tank. Three types of segmental ring models were designed and tested: straight-jointed, stagger-jointed, and uniform rings. The test results indicated that the η values of the stagger-jointed assembly mode were clearly larger than those of the straight-jointed assembly mode under both loading patterns. η increased as the load increased under the realistic loading conditions, whereas η decreased as the load increased under the concentrated load. More importantly, the η values derived from the realistic load tests were considerably larger than those derived from the concentrated load tests for both assembly modes (i.e., 0.423–0.672 and 0.587–0.761 for the straight-jointed and stagger-jointed assembly modes, respectively), and the former should be recommended for practical engineering applications. Furthermore, formulas relating η to the ratio of the cover depth to the tunnel diameter were proposed for sandy soil.